The Pathologic Achilles Insertion Angle (PAIA): A Novel Angular Measurement to Guide Both Evaluation and Treatment of Insertional Achilles Tendinopathy. Issue 4 (November 2022) - Gu, Wanjun; Zhu, Mingjie; Carpenter, Melissa L.; Hunt, Kenneth J.; Myerson, Mark S.; Li, Shuyuan
Category: Hindfoot; Sports Introduction/Purpose: Insertional Achilles tendinopathy (IAT) refers to calcified enlargement of the Achilles insertion. Recently, the Zadek osteotomy has been proven to be an effective and minimally invasive procedure for IAT with a dorsal-based closing wedge osteotomy on the posterior tuberosity of the calcaneus. However, determining the wedge size and location to determine the exact enlargement of the tuberosity remains clinically challenging. The goal of this study was to examine the morphology of the calcaneus in both normal control and IAT groups, and to propose a novel algorithm to determine the angular measurement to guide treatment with a Zadek osteotomy. Methods: Lateral weightbearing images of 40 control feet were used to determine the size of the calcaneus and contour of the tuberosity. The shape of the calcaneus was mapped onto part of a circle the Standard Circle (SC) whose center and radius were statistically fitted and scaled in relation to the height and width of the calcaneus. The diseased tuberosity of 40 patients with IAT was outlined and compared to their respective SC's. An angle was calculated by which the diseased calcaneus curve was rotated around the weightbearing point to fit the SC. We defined this angular measurement as the Pathologic Achilles Insertion Angle (PAIA). The size of the PAIA should be the exact size of the Zadek osteotomy if the apex of the osteotomy is chosen at the weightbearing point of the calcaneus. The effect of moving the apex of the osteotomy anteriorly on the calcaneal pitch angle was calculated. Results: From the morphology of the 40 normal calcanei, the equation of the Standard Curve, R^2=(x+a)^2+(y+b)^2 was created to calculate the SC. The offsets of the center of SC and the radius of SC (a, b, and R) were scaled in relation to the width and height of the calcaneus. From the morphology of the 40 enlarged tuberosities in the IAT group, an algorithm was created to automate the calculation of PAIA. This represented the extent of the enlarged Achilles insertion, which also determined the size and location of the wedge to normalize the contour of the enlarged posterior tuberosity. Using the weightbearing point of the calcaneus as the apex of the osteotomy did not change the pitch angle of the calcaneus, but moving the apex of the osteotomy anteriorly reduced the calcaneal pitch angle determined by both the original PAIA and the calcaneal pitch angle of each specific foot. Conclusion: Based on mechanism of mapping and curve fitting, the newly developed PAIA, will not only guide evaluation of the enlarged tuberosity in IAT, but also calculate the size of the Zadek osteotomy taking the patient's calcaneus size, IAT enlargement size, and pitch angle in consideration.